The International Bank Lending Channel of Monetary Policy Rates and Quantitative Easing : Credit Supply, Reach-for-Yield, and Real Effects - Morais, Bernardo; Peydró, José-Luis; Ruiz, Claudia (World Bank Group, Washington, DC, 2015)
This paper identifies the international credit channel of monetary policy by analyzing the universe of corporate loans in Mexico, matched with firm and bank balance-sheet data, and by exploiting foreign monetary policy shocks, given the large presence of European and U.S. banks in Mexico. The paper finds that a softening of foreign monetary policy increases the supply of credit of foreign banks to Mexican firms. Each regional policy shock affects supply via their respective banks (for example, U.K. monetary policy affects credit supply in Mexico via U.K. banks), in turn implying strong real effects, with substantially larger elasticities from monetary rates than quantitative easing. Moreover, low foreign monetary policy rates and expansive quantitative easing increase disproportionally more the supply of credit to borrowers with higher ex ante loan rates -- reach-for-yield -- and with substantially higher ex post loan defaults, thus suggesting an international risk-taking channel of monetary policy. All in all, the results suggest that foreign quantitative easing increases risk-taking in emerging markets more than it improves the real outcomes of firms.